Implementation of the Zachman Framework in the Digital Sales System in Selotapak Permai Trawas Small and Medium Industries - Felix Handani (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
Small and Medium Enterprise (SMEs) is a community of citizens bringing together entrepreneurs within the scope of small-scale businesses. In SMEs, internal management is spontaneous and generally does not have standardized procedures. The use and utilization of technology can accelerate the growth of procedures that occur in a small industry, but not all of them are successful. Human resource management factors and a culture that has existed for many years shape the uniqueness of its procedures and management. Using the Zachman Framework in the software development process helps analyze needs to obtain concrete requirements according to conditions in the field. Program development using the Software Development Life Cycle by designing, implementing, testing, and validating to users. From the testing and validation results conducting interviews and observations, 15% of community members joined and used the application. With the Zachman Framework, this maturity can be measured properly thereby improving management